PENGENALAN KONSEP BILAGAN MELALUI PEMBELAJARAN DARING PADA ANAK KELOMPOK B DI RA MUSLIMAT NU 15 SUKUN MALANG - Fatima Lagi; Rosichin Mansur; Ika Anggraheni (Jurnal Dewantara, 2021)
At this time all countries in the world, including Indonesia, have been faced with an outbreak of the Covid-19 virus. This covid pandemic has become a major disaster for all mankind, where humans are required to stop from the routine of daily life and are asked to stay at home. The spread of the corona virus in various countries has made major changes in various fields, such as in the economic field, technology, and also has an impact in the field of education. The COVID-19 pandemic requires us to maintain physical distance from those around us (physical distancing). It is not allowed to create a crowd or gather with many people to prevent the spread of COVID-19. From the background of the research above, formulate the research objectives, namely 1) To describe the ability of students to recognize the concept of numbers through online learning at RA Muslimat NU 15 Sukun Malang, 2) How to introduce the concept of numbers through online learning at RA Muslimat NU 15 Malang City, 3) How to understand the concept of numbers through online learning at RA Muslimat NU 15 Sukun Malang. The research was conducted using a qualitative approach with the type of case study research. The data collection procedure is carried out using the observation method, which is a technique or method of collecting data by observing ongoing activities, the interview method, which is a data or information collection tool by asking a number of questions orally to be answered verbally as well as research sources, and the documentation method is collecting data related to the introduction of the concept of numbers through online learning. In conducting data analysis the stages used in this research are data reduction, data presentation, conclusion drawing or verification. While checking the validity of the data using source triangulation, technical triangulation and time triangulation. Researchers act as key instruments, namely as designers, researchers, data collection and knot making. The results of this study conclude that 1) The ability of students to recognize the concept of numbers through online learning in RA. 2) How to introduce the concept of numbers through online learning in RA. 3) How to understand the concept of numbers through online learning at RA Muslimat NU 15 Sukun Malang.